1997
DOI: 10.1021/jp9706644
|View full text |Cite
|
Sign up to set email alerts
|

Early Stages of Copper Electrocrystallization:  Electrochemical and in Situ X-ray Absorption Fine Structure Studies of Coadsorption of Copper and Chloride at the Au(111) Electrode Surface

Abstract: Cu K-edge X-ray absorption spectra (XAS) recorded in situ using glancing incidence and fluorescence detection have been employed to study the codeposition of copper and chloride ions on a Au(111) surface under an electrolyte solution. Chronocoulometric measurements provided information about the composition of the overlayer and about the number of electrons flowing to the interface per adsorbed copper ion. The XAS displays a remarkable dichroism consistent with a bilayer in which the Cu adatoms are covered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 71 publications
9
37
1
Order By: Relevance
“…Both standing wave and computational data favour the structural model where an incommensurate (5×5) Cl layer seen by STM is adsorbed on top of a (1×1) commensurate layer of Cu. Thus, it contrasts studies on Cu-UPD in an acidic environment which conclude either an incommensurate (5x5) CuCl adlayer structure 31,62 or a structure exhibiting significant disorder 40 . Thus adding to the puzzle of Cu-UPD in chloride containing electrolytes, this calls for a detailed comparative study which fully assesses the adsorbate system through a combination of structurally sensitive techniques.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Both standing wave and computational data favour the structural model where an incommensurate (5×5) Cl layer seen by STM is adsorbed on top of a (1×1) commensurate layer of Cu. Thus, it contrasts studies on Cu-UPD in an acidic environment which conclude either an incommensurate (5x5) CuCl adlayer structure 31,62 or a structure exhibiting significant disorder 40 . Thus adding to the puzzle of Cu-UPD in chloride containing electrolytes, this calls for a detailed comparative study which fully assesses the adsorbate system through a combination of structurally sensitive techniques.…”
Section: Discussioncontrasting
confidence: 57%
“…31,37,62,63 This is contrasted by a study using X-ray absorption spectroscopy (XAS) which finds that neither the zincblende structure nor the commensurate layer give satisfactory agreement with the experimental data. 40 The XAS data rule out a narrow distribution of bond distances including the Cu-Cl bond which is not consistent with the models concluded from the STM studies. Suggesting a significant degree of static disorder, the authors surmise that the Cu atoms could be shifted from high symmetry positions.…”
Section: Stmmentioning
confidence: 59%
See 1 more Smart Citation
“…XAS in the hard X-ray region is applied to electrochemical reactions in order to study the local electronic structure of electrolytes in aqueous solutions [216][217][218][219][220]. Hard X-ray photoelectron spectroscopy is applied to investigate potential-induced Si oxide growth in water at the Si membrane surface [221].…”
Section: Electrochemical Reactionsmentioning
confidence: 99%
“…15,16). The effect of chloride on Cu UPD on Au(111), for example, was studied by voltammetry and chronocoulometry, 22,[64][65][66] low energy electron diffraction spectroscopy, 67 X-ray absorption spectroscopy, 24,65 , electrochemical STM 45,[48][49][50]53,[68][69][70] and AFM. 56 In situ STM experiments in sulfuric or perchloric acid revealed that trace amounts of chloride ions lead to the formation of an incommensurate (5 × 5)-like Cu-Cl UPD structure at high potentials.…”
Section: -16mentioning
confidence: 99%